Points of attention when conducting etiological research. Issue 9 (25th March 2021) - Stel, Vianda S.; Chesnaye, Nicholas C.; Tripepi, Giovanni; Dekker, Friedo W.; Zoccali, Carmine; Jager, Kitty J.
Abstract: Epidemiological studies often aim to investigate the causal contribution of a risk factor to a disease or other outcome. In etiological research, one is usually interested in the (biological) mechanism(s) underlying the studied relationship. Inappropriate conduct of an etiological study may have major implications for the correctness of the results and interpretation of the findings. Therefore, in this paper, we aim to describe step by step how etiological research should be carried out, together with its  common pitfalls. These steps involve finding and formulating a well‐defined etiological research question, choosing an appropriate study design including a suitable comparison group, adequate modelling, and adequate reporting and interpretation of the results. SUMMARY AT A GLANCE: A summary of steps to carry out etiological research, including main points of attention.